2002
DOI: 10.1143/jjap.41.l589
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Si3N4 Nanorods from Borosilicate Glass

Abstract: Si 3 N 4 nanorods have been synthesized by nitriding borosilicate glass with ammonia. The formed Si 3 N 4 nanorods exhibit significant crystallization, and are 20 to 80 nm in diameter and 10 to 100 µm in length. Some nanorods are wrapped by amorphous Si 2 N 2 O. The formation of the Si 3 N 4 nanorods is explained based on the vapor-solid growth mechanism; the borosilicate glass substrate and the formation of SiO vapor via a solid-diffusion reaction between boron and silica are responsible for the nanorod growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…It may be considered that the decomposition of iron metal at the tip of SiC is generated above 1500 • C. This reveals that carbothermal reduction process enables to remove metal impurities at tips of SiC nanowires without additional process in spite of material growth via VLS mechanism. Diameters of nanowires grown at various temperatures were not mainly dependent on temperature, since diameters of nanowires grown by VLS mechanism were strongly influenced by droplet size of metal catalyst [38]. Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…It may be considered that the decomposition of iron metal at the tip of SiC is generated above 1500 • C. This reveals that carbothermal reduction process enables to remove metal impurities at tips of SiC nanowires without additional process in spite of material growth via VLS mechanism. Diameters of nanowires grown at various temperatures were not mainly dependent on temperature, since diameters of nanowires grown by VLS mechanism were strongly influenced by droplet size of metal catalyst [38]. Fig.…”
Section: Resultsmentioning
confidence: 89%
“…The droplet is quickly covered with vapor species, reportedly SiO and CO, because of its high accommodation coefficient. In addition, the diameter of SiC nanowire is mainly limited by the size of the iron drops and their surface energy relationship, and undisturbed growth of nanowire is possible [38]. Iron droplet size derived from SiO 2 is very fine in this study, since metallic particles as a catalyst were not intentionally employed into all our experiments.…”
Section: Resultsmentioning
confidence: 99%
“…11,12 Synthesis of one-dimensional silicon nitrides has been explored in the last few years because of their potentials in applications where mechanical strength and hightemperature/corrosive durability are required. Si 3 N 4 nanowires have been synthesized using various methods, such as carbothermal reduction and nitriding reaction at high temperatures, [13][14][15][16][17][18][19] combustion under a high N 2 pressure 20 , and by hot-filament CVD or microwave plasma heating method. 21,22 Zhang et al 23 have demonstrated that Si 3 N 4 nanowires possess much higher bending strength than their bulk counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…Si 3 N 4 nanorods [5][6][7] have been synthesized by mild benzene-thermal route [5], carbothermal reduction [6] and template method [7]. Si 3 N 4 nanowires [8][9][10][11][12][13][14][15][16][17] have been synthesized by carbothermal reduction and nitriding reaction at high temperatures [8][9][10][11][12][13], combustion under a high N 2 pressure [14], hot-filament CVD and microwave plasma heating method [15][16][17]. Most recently, Si 3 N 4 nanobelts have been synthesized via a vapor-solid thermal reaction between ammonia and silicon monoxide [18].…”
Section: Introductionmentioning
confidence: 99%